Predicting and protecting postpartum relationship functioning among heterosexual parents: results from a conflict communication intervention - Murray, Samantha A., author; Braungart-Rieker, Julie, advisor; Brown, Samantha, committee member; Cummings, E. Mark, committee member; Harvey, Ashley, committee member; Luong, Gloria, committee member (Colorado State University. Libraries, 2023)
Postpartum parenting is a critically vulnerable period for parents. Adjusting to life with a new baby often comes with a variety of added stressors, for both new and experienced parents. This family turbulence with which parents must continue to maintain their romantic relationship commonly results in relationship decline. Despite these challenges, parent relationship functioning serves as the bedrock to a healthy family system. Understanding antecedents of the interparental relationship, such as parenting experience (new versus experienced parenthood), parent mental health, and initial relationship functioning, was the preliminary goal for this dissertation. Previous studies have highlighted several factors related to parents' postpartum relationship behavior and satisfaction often from mothers' perspectives; however, gaps remain in our knowledge of fathers' relationship experiences over this life transition. This study fills this gap by specifically investigating predictors of relationship appraisals and behaviors in terms of romantic attachment and constructive conflict behavior for both mothers and fathers. A dynamic change score modeling approach was used to address the secondary goal of the current study: to evaluate whether one parent is driving relationship trajectories for both parents. The third goal of this study was to examine the degree to which a conflict communication intervention, involving mothers and fathers, impacts relationship functioning postpartum. Results suggest an important divergence of the effects of the transition to parenthood for mothers compared to fathers, wherein having additional children may have a more negative impact on mothers' relationship experiences compared to fathers'. Furthermore, these results validate previous research linking parents' mental health to their relationship appraisals (romantic attachment), but not relationship behaviors (constructiveness), and highlight the need to further explore how each parent's mental health influences the other parent's relationship experience over time. In addition, mothers' and fathers' racial profiles played a unique role in their postpartum relationship appraisals and behavior in unexpected ways. Dynamic change score modeling further revealed that changes in mothers' and fathers' romantic attachment over time were co-driven by both parents, while changes in constructive conflict behavior occurred independently. Lastly, the conflict communication intervention appeared to alleviate problematic effects of certain variables for parents' relationship functioning, such as fathers' depressive symptoms on the trajectory of mothers' attachment security. Moreover, mothers may have been particularly benefited by the conflict intervention if they reported more depressive symptoms at the beginning of the study. Overall, the intervention had important protective effects on mothers' and fathers' postpartum behavioral constructiveness but had a limited impact on romantic attachment security. Implications for future interparental relationship and intervention research are discussed.
Keywords: interventions; romantic attachment; transition to parenthood; relationships; constructiveness; trajectories